2014
DOI: 10.1063/1.4894220
|View full text |Cite
|
Sign up to set email alerts
|

Radial convection of finite ion temperature, high amplitude plasma blobs

Abstract: We present results from simulations of seeded blob convection in the scrape-off-layer of magnetically confined fusion plasmas. We consistently incorporate high fluctuation amplitude levels and finite Larmor radius (FLR) effects using a fully nonlinear global gyrofluid model. This is in line with conditions found in tokamak scrape-off-layers (SOL) regions. Varying the ion temperature, the initial blob width, and the initial amplitude, we found an FLR dominated regime where the blob behavior is significantly d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(115 citation statements)
references
References 45 publications
9
106
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] During their radial propagation, the blob-like structures develop a steep front and a trailing wake, which can also be observed in numerical simulations of isolated blob structures [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and simulations of scrape-off layer turbulence. [51][52][53][54][55][56][57][58][59][60][61] Conditional averaging of experimental measurement data have shown that large-amplitude fluctuations are well described by an exponential wave form.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] During their radial propagation, the blob-like structures develop a steep front and a trailing wake, which can also be observed in numerical simulations of isolated blob structures [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and simulations of scrape-off layer turbulence. [51][52][53][54][55][56][57][58][59][60][61] Conditional averaging of experimental measurement data have shown that large-amplitude fluctuations are well described by an exponential wave form.…”
Section: Introductionmentioning
confidence: 99%
“…37 The second point is important as warm ions, which are expected to be present in the edge and SOL region, 38,39 influence the dynamics of turbulence and blob propagation. [40][41][42][43][44][45] The underlying linear normal mode of interest in the present simulations is the interchange mode, importantly modified by the finite ion temperature (cf. Sec.…”
Section: A Equations Of Evolutionmentioning
confidence: 99%
“…This may be used to describe astrophysical plasmas, specifically ionospherical irregularities such as equatorial spread F phenomena, which are thought to be caused by the interchange instability [29 and 44]. The model with α = β = 1 also arises when taking the long wavelength limit of a delta-f gyrofluid model [38] and describes compressible electrostatic motions in a non-uniform magnetic field.…”
Section: Analytic Modelingmentioning
confidence: 99%
“…Within this approximation, which is valid for small particle density perturbations n relative to the background N , | n|/N ≪ 1, one neglects particle density gradients in the inertial terms of the fluid equations while retaining them in the other terms. Recent work avoids this simplification [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%